Result Assessment Tool (RAT): empowering search engine data analysis - Sebastian Sünkler; Dirk Lewandowski; Sebastian Schultheiß; Nurce Yagci (PeerJ Computer Science, 2025)
The Result Assessment Tool (RAT) is a Python-based software toolkit that enables researchers to analyze results from commercial search engines, social media platforms, and library search systems. RAT provides an integrated environment for designing studies, collecting results, and performing automated analysis. The software consists of two main modules: RAT Frontend and RAT Backend. RAT Frontend uses Flask to provide a researcher view for designing studies and an evaluation view for collecting ratings from study participants. RAT Backend includes modules for collecting search results, extracting source code, and adding classifiers for automated analysis. The system has been used in various studies, including search engine effectiveness studies, interactive information retrieval studies, and classification studies.